Collections revisited from the perspective of historical testimonies. (30th September 2019) - Goy, Annamaria; Magro, Diego
This paper presents the results of an ontological analysis of collective entities, as an essential step towards the definition of a rich semantic model underlying ontology-driven applications in the historical and cultural heritage domains. The major contributions of our proposal are the following: (a) An explicit distinction of contingent and necessary features, that led us to formalise our ontology by means of modal logics. (b) A description of collective entities from a diachronic perspective (thus including singletons and empty collections). (c) An analysis of the inferences enabled by the characterisation of collective entities and by the inclusion relationships. (d) A representation of the inclusion relationships that does not imply existential dependence. (e) A distinction between emerging and created collective entities. In this paper, we present an in-depth ontological analysis of these aspects and provide a sound formalisation for it.